İş hukukunda ücretsiz izin - Karabacak, Emre (My University, 2025)
Ücretsiz izin, işçinin iş görme, işverenin ise ücret ödeme borcunun geçici olarak askıya alındığı, ancak iş sözleşmesinin sona ermediği bir durumdur. Çalışmada, ücretsiz iznin kavramsal çerçevesi, hukuki niteliği, türleri, unsurları ve sonuçları detaylı biçimde incelenmiştir. Ücretsiz izin, iradi ve kanuni ücretsiz izin olmak üzere iki ana türde ele alınmaktadır. Tarafların serbest iradesiyle yapılan ücretsiz izin uygulamaları ile kanundan kaynaklanan tek taraflı ücretsiz izin hakları çalışmamızda karşılaştırılmıştır. Ayrıca ücretsiz iznin iş sözleşmesine, tarafların hak ve borçlarına, kıdeme bağlı haklara, sosyal güvenlik durumuna ve toplu iş hukukuna etkileri değerlendirilmiştir. Mevzuattaki dağınıklık ve yetersizlik, uygulamada çeşitli hukuki sorunlara yol açtığından, düzenleme önerilerine de yer verilmiştir. Çalışmada, belirli süreli, asgari ve azami süreli iş sözleşmelerinde; üçlü iş ilişkilerinde ücretsiz izin durumları değerlendirilmiş, ücretsiz iznin deneme süresine etkisi, diğer askı süreleriyle çakışması ve nafaka ve icra borçlarına etkisi ele alınmıştır. Sonuç olarak, hem bireysel hem toplu iş ilişkileri açısından ücretsiz iznin hukuki çerçevesinin netleştirilmesi, iş barışı ve sosyal güvenlik açısından önem arz etmektedir.

Unpaid leave constitutes a legal mechanism wherein the employee’s obligation to perform work and the employer’s obligation to pay wages are temporarily suspended, without resulting in the termination of the employment contract. This dissertation offers a comprehensive analysis of the conceptual foundations, legal nature, classifications, constitutive elements, and legal consequences of unpaid leave within the framework of labor law. Unpaid leave is examined under two principal categories: voluntary unpaid leave, which arises from mutual agreement between the parties, and statutory unpaid leave, which is grounded in legal entitlements and may be exercised unilaterally. The study systematically compares these two forms, while also evaluating the implications of unpaid leave on the employment relationship, the reciprocal rights and obligations of the parties, entitlements linked to seniority, social security coverage, and the domain of collective labor law. Given the current legislative fragmentation and insufficiency, the study further provides normative proposals to enhance legal clarity and consistency in practice. In the dissertation, the application of unpaid leave in fixed-term and duration-specific employment contracts, as well as within tripartite employment relationships have been analyzed. The interaction between unpaid leave and probationary periods, its concurrence with other suspension mechanisms, and its effects on enforcement of alimony and debt obligations are also explored. Ultimately, establishing a well-defined legal framework for unpaid leave is crucial, in order to safeguard both individual and collective employment relations, ensure legal certainty, and support the broader objectives of labor peace and social protection.
Unpaid leave in labor law
Keywords: Askı Hali; Aylıksız İzin; İş hukuku; İzin; Labor laws and legislation; Leave; Leave without Salary; Suspension; Turkey; Türkiye; Unpaid Leave; Ücretsiz İzin